Time continuum of journalistic texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article attempts to analyze the temporal continuum of the texts of Ukrainian journalism, to determine the peculiarities of the sense of time Ukrainians.
Keywords: continuum; discourse; time; temporal; publicity texts